PENDAPATAN USAHA TANI BIBIT CABAI DI CV.TUNAS INTI AGRI MAKMUR DESA LUWUS KABUPATEN TABANAN - I Made Restu; Ida Ayu Made Dwi Susanti; Ni Putu Anglila Amaral, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2022)
Tunas Inti Agri Makmur is one of the local companies engaged in agriculture especially the seed industry such as chili, gumitir, eggplant and papaya. CV. Tunas Inti Agri Makmur continuously innovates in the field of research and development so that it can produce seeds that have the best new varieties. One of the superior products in CV. Tunas Inti Agri Makmur are chili seeds. The purpose of this study was to analyze the amount of income obtained from chili seed farming and to find out the obstacles faced by CV. Tunas Inti Agri Makmur Luwus village, Tabanan Regency. This research was conducted from October to November 2021. The location of this research was determined by the purposive sampling method while the respondent of this study was determined by census method, so the sample inthis study as many as 12 respondents. The data analysis methods used in this study are income analysis methods and descriptive analysis methods. Based on the results of research in CV. Tunas Inti Agri Makmur Luwus village, Tabanan Regency can be concluded as follows : The average income obtained by chili seed farming in one month in each harvest day amounted to Rp. 16.350.141,67 obtained from the average revenue of chili seed farming of Rp. 72.975.000 and the total production cost of Rp. 56.616.858,33. There are two obstacles, namely Internal obstacles and External obstacles.